Tax Compliance: An Experimental Approach - Kristian Agung Prasetyo; Suhut Tumpal Sinaga (Hasanuddin Economics and Business Review, 2017)
In a self-assessment system, the tax office has a passive position. Their main duty of the tax office is to ensure that taxes that are calculated and paid by the taxpayers are in accordance with the applicable tax rules. The main instrument for this purpose is, in an income tax context, the income tax return. Based on the information written by taxpayers in this form, the tax office then conducts a set of activities to see of the tax return contains information that reflects taxpayer’s reality.The self-assessment system carries a consequence that taxpayer compliance has a major role in determining the amount of taxes that are collected by the tax office. If the taxpayers comply with the tax rules, then consequently, more tax revenue will be collected. On the contrary, if the compliance rate is low, then there will be less revenue.This research looks at this issue. The focus is individual taxpayers as their contribution to the total revenue currently is low. For this purpose, this research uses an experimental approach using participants from students at the PKN STAN (from both school leavers and civil servants), tax trainers at the Pusdiklat Pajak, and newly-recruited employees of the tax office. The experiment reveals that firstly, on average the research participants report less income that it should have been reported. Secondly, it is revealed that audit rate and penalty rate are the two most important factors in influencing the amount of income reported by the research participants.